The ALMT Family of Organic Acid Transporters in Plants and Their Involvement in Detoxification and Nutrient Security - Sharma, Tripti; Dreyer, Ingo; Kochian, Leon; Piñeros, Miguel A. (Frontiers in Plant Science, 2016)
About a decade ago, members of a new protein family of anion channels were discovered on the basis of their ability to confer on plants the tolerance towards toxic aluminum ions in the soil. The efflux of Al3+-chelating malate anions through these channels is stimulated by external Al3+ ions. This feature of a few proteins determined the name of the entire protein family as Aluminum-activated Malate Transporters (ALMT). Meanwhile, after several years of research, it is known that the physiological roles of ALMTs go far beyond Al-detoxification. In this review article we summarize the current knowledge on this transporter family and assess their involvement in diverse physiological processes.